Sustainability in the Companies Practices (European Journal of Marketing and Economics, 2022)
The sustainability topic is present in our everyday life. No matter if we are traveling in the public transport, we are having coffee with friends or watching tv we hear something related to green economy, sustainable usage of resources or smart energy saving devices. All ads that we see around us, in one way or another, also are calling to be environmentally friendly and sustainable. On national and international level, there are a lot of regulations and requirements developed and enforced both for the business and for the citizens. In the general case, it is commonly accepted, that the companies are taking actions in the field of sustainable development only because they are forced to do so by legislative requirements and penalties. But is it always the case? The paper discusses the main idea standing behind the sustainable development and presents some of the models that summarizes this idea. Further, by reviewing the practices of three large companies in different economic fields, it discusses their approach and attitude towards the subject. Key words: Sustainability, environment protection, business practices
Keywords: words: Sustainability, environment protection, business practices